Tokyo: art and photography - Fritsch, L (Ashmolean Museum, University of Oxford, 2021)
This book is a celebration of Tokyo: one of the world's most creative, dynamic and fascinating cities. Beautifully illustrated and richly detailed, this publication looks at a city which has undergone constant destruction and renewal over its 400-year history and tells the stories of the people who have made Tokyo so famous with their boundless drive for the new and innovative - from samurai to avantgarde artists today.